Single Tariff of Income Tax, The Principle of Fairness And Business Competitiveness Advantage - Johny Budiman (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this research is to find out and gain an understanding of the single tax rate and the principle of justice. This research is a literature study related to the tax system in Indonesia, tax regulations, taxation principles, describe and explain their relationship and impact on the business world. The conclusion is that the government continues to strive to facilitate and pay attention to the sense of justice for taxpayers. Progressive rates or single rates, corporate taxpayers still get a sense of justice. The single rate does not reflect vertical justice, but horizontal justice will still be met. The implementation of a single and final tax rate is expected to fulfill the aspects of simplicity, elements of justice, and the principles of social justice as much as possible for the welfare of the people. Support for the business world, such as the provision of tax incentives can increase the productivity and competitiveness of MSMEs